Reduced impact logging of gmelina plantation in Omo Forest Reserve, Nigeria (2005)
Logging induced damages associated with two different harvesting systems (Conventional Timber Harvesting and Reduced-Impact Logging (RIL) were investigated in 1984 compartment of Gmelina arborea plantation in Omo Forest Reserve. The same equipment and felling crew were used for both methods. Felling was done using heavy chainsaw (Stihl 070) and skidding was carried out with crawler tractor. The types and severity of damage to the residual stand were determined for felling and skidding operations in both methods using visual assessment. Data collected were analyzed using a combination of percentages and descriptive statistics. The residual stand based on tree population were 68.28% for conventional logging and 34.88% for reduced-impact logging. The degree of damage was based on severity of injuries on individual trees. These were categorized as light injury, medium injury and heavy injury. Values obtained for the three categories of injury were 16.36, 11.06 and 42.0 1% and 5.34, 7.16 and 22.41% for conventional wood harvesting and reduced-impact logging respectively. This result shows that RIL, has the potential of considerably minimizing damages to residual stand by almost half when properly carried out.